2017
DOI: 10.1055/s-0037-1599056
|View full text |Cite
|
Sign up to set email alerts
|

Residents' Learning Curve of Lumbar Transforaminal Epidural Steroid Injections

Abstract: Background and Study Aims There is a paucity of literature on beginners' training and on its connection with patient safety for transforaminal epidural steroid injections (TFESIs). This study retrospectively assessed the learning curves and associated complications of neurosurgery residents never previously exposed to TFESI and compared them with experienced board-certified faculty neurosurgeons (BCFNs). Material and Methods Procedure time in minutes, dose-area product (DAP) in cGy*cm2, periprocedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In one study of residents’ learning curve with lumbar TFESI, residents took more time and required more fluoroscopy in TFESI of S1 than for the upper lumbar nerve roots. [ 13 ] In our study, an OS approach to the S1 foramen was effective, easy, and faster than the AP approach. In the report that first introduced the oblique approach, researchers mentioned potential advantages of it, including reduced procedure time and radiation exposure.…”
Section: Discussionmentioning
confidence: 67%
“…In one study of residents’ learning curve with lumbar TFESI, residents took more time and required more fluoroscopy in TFESI of S1 than for the upper lumbar nerve roots. [ 13 ] In our study, an OS approach to the S1 foramen was effective, easy, and faster than the AP approach. In the report that first introduced the oblique approach, researchers mentioned potential advantages of it, including reduced procedure time and radiation exposure.…”
Section: Discussionmentioning
confidence: 67%
“… 8 , 11 During spinal procedures, especially when performing STEB at the L5/S1 level, it is often difficult to identify the target point and secure the entry path of the needle because of the pelvic bone. 10 Therefore, the phantom designed in the present study could also be useful for training and simulating transforaminal endoscopy or other procedures in which the pelvic bones may cause difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of using phantoms to teach procedures. 5 , 8 , 10 13 However, to the best of our knowledge, this is the first study to evaluate the efficacy of simulation phantoms for training in the performance of selective transforaminal epidural block (STEB), medial branch block (MBB), and lumbar sympathetic ganglion block (LSGB) procedures. In addition, standard tools to evaluate the learning effects of these procedures are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Most reports on learning curves or variability across practitioners for invasive treatments for neck or low back pain focus on interventions other than NRT, many of which lack high quality evidence supporting their efficacy and effectiveness. Moreover, they are based on small samples (e.g., ≤150 patients or ≤3 practitioners), do not use multi-level analyses to adjust results for patient prognosis as established by previously validated models, or have been conducted either retrospectively or outside routine practice conditions (e.g., based on data gathered in randomized controlled trials) [ 8 , 9 , 10 , 11 , 12 , 13 , 40 , 41 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Therefore, it is inappropriate to compare such data with results from this study.…”
Section: Discussionmentioning
confidence: 99%